2015
DOI: 10.3171/2015.6.focus15216
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic short-term follow-up after surgical decompression of the median nerve at the carpal tunnel: a single-center prospective observational study

Abstract: OBJECT Carpal tunnel syndrome causes increased cross-sectional area (CSA) of the median nerve, which can be assessed by high-definition ultrasonography. It is unclear today, however, whether high-definition ultrasonography may play a role in the postoperative period. This prospective study aimed to determine the natural history of the morphology of the median nerve at the carpal tunnel after surgical decompression assessed by high-definition ultrasonography. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
22
1
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 17 publications
3
22
1
3
Order By: Relevance
“…Comparing these results with previously published studies examining the postoperative proximal median nerve CSA after CTR is challenging because of methodological differences with respect to patient populations, US equipment, measurement techniques, operator experience, and follow‐up periods. Nonetheless, the quantitative reductions in the CSA observed in this investigation are similar to those reported previously for open CTR, endoscopic CTR, and the single published case report of US‐guided CTR …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Comparing these results with previously published studies examining the postoperative proximal median nerve CSA after CTR is challenging because of methodological differences with respect to patient populations, US equipment, measurement techniques, operator experience, and follow‐up periods. Nonetheless, the quantitative reductions in the CSA observed in this investigation are similar to those reported previously for open CTR, endoscopic CTR, and the single published case report of US‐guided CTR …”
Section: Discussionsupporting
confidence: 90%
“…Postoperative median nerve CSA reductions appear to be similar among patients treated with open and endoscopic CTR, and in both cases, the reduction in the median nerve CSA has been interpreted to represent a reduction in intraneural edema as a result of successful TCL transection . Despite the improvement in median nerve CSA after open and endoscopic CTR, the CSA does not necessarily return to normal even at long‐term follow‐up in clinically improved patients . The precise reason for these observations is unknown but may be reflective of permanent structural changes within the median nerve (eg, fibrosis).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These advantages make ultrasonography a useful tool for making comparisons before and after surgery. Previous reports indicated that the enlarged median nerve CSA seen in CTS can shrink after surgery [12][13][14][15], and this is consistent with the present findings. About the displacement of median nerve induced by finger movement, Yoshii reported no significant changes after carpal tunnel release [16].…”
Section: Discussionsupporting
confidence: 93%